RATIO OF TRIGLYCERIDES TO HIGH-DENSITY LIPOPROTEIN CHOLESTEROL AND MARKERS OF LIVER INJURY IN DIABETES MELLITUS - VARADHAN, SOWMYA; SIMON A, SUPRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: The present study was done to evaluate and compare the triglyceride to high-density lipoprotein (TG/HDL) ratio in subjects with diabetes mellitus (DM) and diabetic prone subjects (impaired glucose tolerance [IGT]) with normal subjects without diabetes. An attempt was also made to correlate TG/HDL with markers of liver injury such as alanine aminotransferase, aspartate aminotransferase, (AST), and alkaline phosphatase (ALP). Methods: Lab data of 496 patients attending Pushpagiri medical health checkup were obtained. The subjects were grouped into DM: (fasting plasma glucose >126 mg/dl), IGT: (Fasting plasma glucose: 110-126 mg/dl) and normal: (fasting plasma glucose < 110 mg/dl). Results: Statistically significant difference were observed in levels of TG, low-density lipoprotein (LDL), TG/HDL ratio, AST, ALP between diabetes, IGT and normal subjects. Statistical significance within the groups was tested using post-hoc Analysis. The level of TG and TG/HDL ratio was significantly higher in subjects with DM compared to normal subjects. The mean value of total cholesterol and LDL-C was found to be higher in normal subjects than in DM and IGT. AST, ALP values were found to be significantly higher in subjects with IGT than normal subjects. Conclusion: From this study, it can be concluded that TG and TG/HDL ratio were high in DM and IGT than subjects with normal plasma glucose. Liver injury marker enzymes were found to be high in IGT and is correlated with TG/HDL ratio in DM. Keywords: Diabetes mellitus, Impaired glucose tolerance, Hypertriglyceridemia, Triglyceride to high-density lipoprotein ratio, Markers of liver injury.